(untitled) (Transactions of the Association of European Schools of Planning, 2022)
The forgotten Italian territories have almost always been understood as compact physical and conceptual spaces. While changing its terms, borders, and issues from time to time, the forgotten regions have been described through a homogeneous image: Mezzogiorno, peripheries and Inner Areas. Such a representation has effects both in conceptualization and efforts taken to recompose the gaps between the forgotten territories and the most active parts. Yet, in recent years, the numerous crises of the 21st century have shattered this compact representation and brought out new geography of forgotten Italy, the Italia di mezzo. The new geography is no longer linked only to the North-South dichotomy and does not concern only the metropolitan suburbs or inland areas. The new geography highlights how to be forgotten now is also a piece on the margins of public policies, underestimated by scientific research but at the center of the twentieth-century urbanization process and the recent crisis.